The novel persistent sodium current inhibitor PRAX‐562 has potent anticonvulsant activity with improved protective index relative to standard of care sodium channel blockers. Issue 3 (17th January 2022) - Kahlig, Kristopher M.; Scott, Liam; Hatch, Robert J.; Griffin, Andrew; Martinez Botella, Gabriel; Hughes, Zoë A.; Wittmann, Marion
Abstract: Objective: This study investigates the effects of PRAX‐562 on sodium current (INa ), intrinsic neuronal excitability, and protection from evoked seizures to determine whether a preferential persistent INa inhibitor would exhibit improved preclinical efficacy and tolerability compared to two standard voltage‐gated sodium channel (NaV ) blockers. Methods: Inhibition of INa was characterized using patch clamp analysis. The effect on intrinsic excitability was measured using evoked action potentials recorded from hippocampal CA1 pyramidal neurons in mouse brain slices. Anticonvulsant activity was evaluated using the maximal electroshock seizure (MES) model, and tolerability was assessed by measuring spontaneous locomotor activity (sLMA). Results: PRAX‐562 potently and preferentially inhibited persistent INa induced by ATX‐II or the SCN8A mutation N1768D (half‐maximal inhibitory concentration [IC50 ] = 141 and 75 nmol·L –1, respectively) relative to peak INa tonic/resting block (60× preference). PRAX‐562 also exhibited potent use‐dependent block (31× preference to tonic block). This profile is considerably different from standard NaV blockers, including carbamazepine (CBZ; persistent INa IC50 = 77 500 nmol·L –1, preference ratios of 30× [tonic block], less use‐dependent block observed at various frequencies). In contrast to CBZ, PRAX‐562 reduced neuronal intrinsic excitability with only a minor reduction in action potential amplitude. PRAX‐562 (10 mg/kg po) completely prevented evoked seizures without affecting sLMA (MES unbound brain half‐maximal efficacious concentration = 4.3 nmol·L –1, sLMA half‐maximal tolerated concentration = 69.7 nmol·L –1, protective index [PI] = 16×). In contrast, CBZ and lamotrigine (LTG) had PIs of approximately 5.5×, with significant overlap between doses that were anticonvulsant and that reduced locomotor activity. Significance: PRAX‐562 demonstrated robust preclinical anticonvulsant activity similar to CBZ but improved compared to LTG. PRAX‐562 exhibited significantly improved preclinical tolerability compared with standard NaV blockers (CBZ and LTG), potentially due to the preference for persistent INa . Preferential targeting of persistent INa may represent a differentiated therapeutic option for diseases of hyperexcitability, where standard NaV blockers have demonstrated efficacy but poor tolerability.